Recrystallization in the metal of welding joints of steam trucks - Dmytryk, V. V.; Glushko, A. V.; Tsaryk, A. K. (My University, 2019)
The recrystallization process in the structure of welded joints of steam pipelines from heat-resistant pearlitic steels, operated for a long time under creep conditions (Te = 545…585 °С, Рe = 20…25 MPa), reduces their performance. Studying the peculiarities of the recrystallization process will allow slowing down its passage, which is important for increasing the service life of welded joints of steam pipelines, which are characterized by the presence of a certain structural heterogeneity.

Процес рекристалізації в структурі зварних з'єднань паропроводів із теплостійких перлітних сталей, які тривалий час працюють в умовах повзучості (Те = 545…585 °С, Ре = 20…25 МПа), сприяє зниженню їх експлуатаційних характеристик. Вивчення особливостей процесу рекристалізації дозволить уповільнити їх проходження, що актуально для збільшення ресурсу зварних з'єднань паропроводів, що характеризуються наявністю певної структурної неоднорідності.
Рекристалізація в металі зварних з'єднань паропроводів
Keywords: the recrystallization process; welded joints; steam pipelines; процес рекристалізації; теплостійкі перлітні сталі; зварні з'єднання; повзучість